2022
DOI: 10.1021/acs.energyfuels.2c03244
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Analysis of Shale Gas Adsorption under Carbon Dioxide–Moisture Conditions: A Molecular Dynamic Study

Abstract: In recent decades, shale gas, which has been regarded as a source of clean energy, is gradually replacing conventional energy. Shale gas adsorption in carbon dioxide (CO2)–moisture systems has been discussed in many previous studies; however, the intrinsic mechanism has not been clarified yet. In this work, the molecular dynamic (MD) method is adopted to study the adsorption behaviors of shale gas adsorption in the realistic kerogen nanoslit. The spatial density distributions of shale gas and different compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
3
5
0
Order By: Relevance
“…With a mesh size of 0.5 Å, the simulation domain was chunked, and the density value was derived by counting the atomic numbers present in each chunk within the simulation domain. Due to van der Waals interactions between carbon and total fluid atoms, density peaks appeared at the interface between the fluid and graphene layers, and consequently, multilayers formed, as proved in previous studies [ 38 , 39 ]. It can be observed that the sodium ions are concentrated on the left side of the electrode due to the electric field force.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…With a mesh size of 0.5 Å, the simulation domain was chunked, and the density value was derived by counting the atomic numbers present in each chunk within the simulation domain. Due to van der Waals interactions between carbon and total fluid atoms, density peaks appeared at the interface between the fluid and graphene layers, and consequently, multilayers formed, as proved in previous studies [ 38 , 39 ]. It can be observed that the sodium ions are concentrated on the left side of the electrode due to the electric field force.…”
Section: Resultssupporting
confidence: 76%
“…This structure also has a confined effect on the fluid molecules, especially at the beginning and ending positions of the nanochannel, which is similar to the phenomenon of ion rejection. between carbon and total fluid atoms, density peaks appeared at the interface between the fluid and graphene layers, and consequently, multilayers formed, as proved in previous studies [38,39]. It can be observed that the sodium ions are concentrated on the left side of the electrode due to the electric field force.…”
Section: Spatial Distributions Of Ions In the Protein Nanochannelsupporting
confidence: 75%
“…Geological sequestration of carbon dioxide (CO 2 ) has been considered a promising solution to mitigate the adverse effects of climate change by stemming the increase in atmospheric CO 2 (Bachu, 2000; Falkowski et al., 2000; J. Liu et al., 2022). There are several options for sites used for geological CO 2 storage, such as deep saline aquifers, depleted oil and gas reservoirs, unmineable coal seams, etc.…”
Section: Introductionmentioning
confidence: 99%
“…
Geological sequestration of carbon dioxide (CO 2 ) has been considered a promising solution to mitigate the adverse effects of climate change by stemming the increase in atmospheric CO 2 (Bachu, 2000;Falkowski et al, 2000;J. Liu et al, 2022).
…”
mentioning
confidence: 99%
“…They found that CH 4 surface adsorption is strongly dependent upon surface wettability and that adsorption capacity in organic-rich shales can be much higher than that in inorganic-rich shales. Liu et al 18 investigated CH 4 adsorption in the presence of CO 2 and moisture in realistic kerogen slits using MD simulations. They observed that H 2 O prefers to adsorb on the oxygen-enriched position and CO 2 tends to adsorb on the carbon-rich site.…”
mentioning
confidence: 99%